2012
DOI: 10.1021/ic300853f
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Iron(II) Spin-Crossover Grafted Phosphazene Polymer

Abstract: Two new cyclotriphosphazene ligands with pendant 2,2':6',2″-terpyridine (Terpy) moieties, namely, (pentaphenoxy){4-[2,6-bis(2-pyridyl)]pyridoxy}cyclotriphosphazene (L(1)), (pentaphenoxy){4-[2,6-terpyridin-4-yl]phenoxy}cyclotriphosphazene (L(2)), and their respective polymeric analogues, L(1P) and L(2P), were synthesized. These ligands were used to form iron(II) complexes with an Fe(II)Terpy(2) core. Variable-temperature resonance Raman, UV-visible, and Mössbauer spectroscopies with magnetic measurements aided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…This is supported by the colour of the solution and solubility of the complexes. Unlike the metallo-polymers previously reported by us [5,13] both L 1 -Fe and L 2 -Fe, could be dissolved in THF and chloroform and dried repeatedly, suggesting little or no cross-linking.…”
Section: Inorganic Chemistry Communications J O U R N a L H O M E P Amentioning
confidence: 63%
See 3 more Smart Citations
“…This is supported by the colour of the solution and solubility of the complexes. Unlike the metallo-polymers previously reported by us [5,13] both L 1 -Fe and L 2 -Fe, could be dissolved in THF and chloroform and dried repeatedly, suggesting little or no cross-linking.…”
Section: Inorganic Chemistry Communications J O U R N a L H O M E P Amentioning
confidence: 63%
“…This could be avoided by reacting FeCl 2 ·4H 2 O with the free ligand followed by anion metatheses [15,16]. However, we have previously described attempts at anion exchange with non-coordinated anions resulting in incomplete reactions [5] which will be exacerbated Scheme 1. The substituted tricyclophosphazene, N 3 P 3 (bph) 2 (Obpy) 2 .…”
Section: Inorganic Chemistry Communications J O U R N a L H O M E P Amentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that varying the spacer between the phosphazene and the metal complex alters the physical behaviour of the complexes [2,3]. Since this behaviour is generally similar for the cyclotrimer and the polymer, the former can be used as a model for the polymer [2,3].…”
Section: Introductionmentioning
confidence: 98%